Colorado's Voucher Law:Examining the Claim of Fiscal Neutrality - Welner, Kevin G. (Education Policy Analysis Archives, 2004)
Colorado's voucher law was declared unconstitutional by the Colorado Supreme Court on June 28, 2004. Voucher supporters have begun drafting revised legislation designed to address the legal problem. This article calls into question the key financial claim of revenue neutrality'a claim that was central to the promotion and passage of the departing voucher law. The author concludes that the voucher law was not revenue neutral, even though it attempts to exclude from eligibility those children already enrolled in private schools. In fact, this law, as well as any revised law with similar eligibility provisions, would actually cost taxpayers an additional $10 million per year once fully implemented because the eligibility provision provides little more than a short-term damper on the law's long-term fiscal impact.